The effect of squash training on shoulder girdle mobility and frequency of injury among player - Mikołaj Gajewski; Magdalena Alcer; Ewa Grygierzec; Karol Jabłoński; Justyna Szefler - Derela (Kazimierz Wielki University, 2017)
Introduction: Squash is a relatively new field in the Polish sports market. Its specification is based primarily on dynamic movements, often taking place at the end of its scope. This condition is an increased risk of injury as well as numerous compensations throughout the body. Aim: The aim of the study was to examine the impact of squash training on shoulder mobility of active athletes and to identify factors likely to increase trauma among players. Does squash game cause hypermobility in all dimension? Do long-term breaks in squash training increase the frequency of injuries? Does pre-training warm up affect trauma? Material and method: The study consists 110 active players: 19 women (17%) and 91 men (83%) age between 17 and 50 years. The research tool was an author's questionnaire consisting of metrics and closed questions, which examined the problem and testing the mobility of the shoulder girdle using  an inclinometer and functional tests. Descriptive statistics were made. The greatest limitation of the range of motion in the shoulder joint is observed in the sagittal plane - flexion. No injury was associated with a prolonged break from training. Conclusion: Squash players did not have hypomobility in the shoulder joint and even had a limited range of motion. Long-term breaks in squash training do not increase the level of trauma.